STRATEGI DALAM MENINGKATKAN MOTIVASI BERWIRAUSAHA BAGI MAHASISWA JURUSAN EKONOMI SYARIAH DI INSTITUT AGAMA ISLAM (IAI) AGUS SALIM METRO LAMPUNG - Zainal arifin (Jurnal At Taajir, 2021)
Abstrack: The role of the campus is to instill an entrepreneurial spirit in its graduates and inspire them to pick out entrepreneurship as a career through the implementation of entrepreneurship education. Universities need to follow positive mastering patterns. All universities which include the Institute of Islamic faith (IAI) Agus Salim Metro as destiny graduates ought to make certain efforts to put together their graduates for independence and competitiveness. This research is a field research (Filed research), namely the look for area records (research locations) due to the fact the studies completed is related to the hassle or truth. This studies makes use of a qualitative method with records collection strategies through surveys and interviews. The item of this research is entrepreneurial motivation, while the challenge of this research is the 2020 Islamic Economics primary. The results of this have a look at imply that the approach to boom the entrepreneurial spirit for college kids, specifically via formal education, via entrepreneurship seminars and thru entrepreneurial internships and motivates students to need to open a commercial enterprise. whenever you perform a method, there need to be inhibiting and helping elements, as well as the department of Islamic Economics, which has boundaries and supports. The inhibiting factors are the students themselves who're nevertheless not interested by entrepreneurship, and the supporting factor is the collaboration with the business global.